Brucellosis in the UK: a risk to laboratory workers? Recommendations for prevention and management of laboratory exposure. Issue 1 (21st May 2008) - Reddy, S; Manuel, R; Sheridan, E; Sadler, G; Patel, S; Riley, P
Abstract : Brucella spp is an uncommon class 3 pathogen isolated in laboratories serving non-endemic areas. This is a report of four recent cases of brucellosis diagnosed at five different London laboratories, and it highlights the need to maintain a high index of suspicion for brucellosis in patients with a history of travel to and/or consumption of unpasteurised foods from endemic areas. A protocol for risk categorisation is proposed, and there is a description of the strategy adopted for serological follow-up of exposed staff and use of postexposure prophylaxis.